(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article discusses the issues of mathematical modeling of non-stationary filtration processes of liquids in porous media and their study using numerical methods using the MATLAB software environment. In the study, a mathematical model was developed based on Darcy’s law and mass conservation equations describing the movement of liquids in porous media. The resulting partial differential equation was discretized using the finite difference method and numerical solutions were obtained in the MATLAB environment. The calculation results made it possible to determine the distribution of pressure in time and space inside the porous media. The obtained results show that numerical modeling methods are an effective tool in studying filtration processes in porous media.